Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Using the method of undetermined coefficients.

Guess $(Ax+B)e^x$

Plug into diff eq:

$-3[(Ax+B)e^x]'' - 2[(Ax+B)e^x]' + (Ax+B)e^x = 3xe^x$

Wolfram alpha simplifies this to: $A(x-2)=e^x(4B+3x)$. Solving for A and B we find $A = 3e^3$ and $B = -6/4$.

Thus, we have $y_p = [3xe^3-(6/4)]e^x$ but this is incorrect. What am I doing wrong here?

share|improve this question
1  
You must solve the equation for all $x$, leave $x$ a unknown. There is no such solution for the simplified equation you got from wolfram alpha, since the $e^x$ term gets in the way. Are you sure you entered the equatin correctly? –  fgp Oct 20 '12 at 0:09

2 Answers 2

up vote 1 down vote accepted

I get

$$A=-\frac{3}{4}\;\;,\;\;B=\frac{3}{2}$$

and everything's peachy...So either you fed WA with wrong data or WA is wrong.

share|improve this answer

$$(Axe^x+Be^x)'=Axe^x+(A+B)e^x$$

$$(Axe^x+Be^x)''=Axe^x+(2A+B)e^x$$

Using that, I get

$$-3A-2A+A=-4A=3$$

$$-3(2A+B)-2(A+B)+B=-8A-4B=0$$

$$B=-2A$$

That seems to agree with DonAntonio's solution.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.